Dystocia in Rathi cows due to congenital hydrocephalus - PUROHIT, G N; GAUR, M; SHARMA, ARVIND (The Indian Journal of Animal Reproduction, 2023)
Three cases fo dystocia due to congenital hydrocephalus fetus in cows were successfully delivered per-vaginally.
Keywords: Cow; hyprocephalus; fetus